Defining the normal range of fractional exhaled nitric oxide in children: one size does not fit all. Issue 3 (12th September 2022) - Wang, Ran; Fowler, Stephen J.; Turner, Stephen W.; Drake, Sarah; Healy, Laura; Lowe, Lesley; Wardman, Hannah; Bennett, Miriam; Custovic, Adnan; Simpson, Angela; Murray, Clare S.
Background: The normal range of fractional exhaled nitric oxide ( F ENO ) is influenced by demographic factors. However, single, fixed cut-off values are used for clinical interpretation in children despite rapid growth. We aimed to define the normal range of F ENO during childhood and evaluate its utility in a diagnostic setting. Method: F ENO percentile charts were developed using data from nonasthmatic children in a population-based birth cohort (Manchester Asthma and Allergy Study). Children were skin prick tested, F ENO measured at the ages of 8, 11, 13–16 and 18 years and clinical information collected. This chart was externally validated in the Study of Eczema and Asthma to Observe the Influence of Nutrition (SEATON) cohort before being prospectively tested in symptomatic, treatment-naïve patients with suspected asthma in a diagnostic setting (Rapid Access Diagnostics for Asthma study). Results: Height, weight, body mass index and age were predictive of F ENO in univariate analysis using 1220 F ENO measurements. Only height remained significant after adjustment in the overall, nonatopic and atopic populations, and was included in the predictive equations for 50th, 75th 90th and 98th percentiles. The proposed percentile lines corresponded to the 57th (95% CI 53rd–61st), 80th (76th–83rd), 90th (87th–92nd) and 98th (96th–99th) percentiles in the SEATON cohort (660 measurements). When tested in 73 symptomatic treatment-naïve children and young adults (median (interquartile range) age: 11 (8–14) years), an F ENO >90th percentile gave a 96% specificity and positive predictive value of 97%, identifying 59% of children who were subsequently diagnosed with asthma after extensive testing. Conclusion: We developed a height-based F ENO percentile chart which quantifies the probability of asthma in symptomatic children and merits further validation towards clinical implementation. As height increases rapidly and substantially during childhood, a single F ENO cut-off for asthma diagnosis may not be appropriate in children. A validated height-adjusted F ENO centile chart can be easily and effectively used in the asthma diagnostic process. https://bit.ly/3nQs2PS